MSC Transplantation Attenuates Inflammation, Prevents Endothelial Damage and Enhances the Angiogenic Potency of Endogenous MSCs in a Model of Pulmonary Arterial Hypertension - Shao F; Liu R; Tan X; Zhang Q; Ye L; Yan B; Zhuang Y; Xu J (Dove Medical Press, 2022)
Fengjin Shao,1- 3 Rui Liu,1 Xun Tan,1- 4 Qiaoyan Zhang,1- 3 Lujie Ye,1- 3 Bingxuan Yan,1- 3 Ying Zhuang,1,2,4 Jiaxue Xu1,2,4 1Department of Veterinary Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of China; 2Veterinary Medical Center, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of China; 3Institute of Preventive Veterinary Sciences, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of China; 4Hainan Institute of Zhejiang University, Sanya, Hainan Province, People's Republic of ChinaCorrespondence: Xun Tan, Department of Veterinary Medicine, Zhejiang University, Yuhangtang Road 866, Hangzhou, 310058, People's Republic of China, Tel +86 571 8898 2393, Fax +86 571 8898 2310, Email tanxun@zju.edu.cnPurpose: Pulmonary arterial hypertension (PAH) is a progressive and fatal pulmonary vascular disease initiated by endothelial dysfunction. Mesenchymal stromal cells (MSCs) have been shown to ameliorate PAH in various rodent models; however, these models do not recapitulate all the histopathological alterations observed in human PAH. Broiler chickens (Gallus gallus) can develop PAH spontaneously with neointimal and plexogenic arteriopathy strikingly similar to that in human patients. Herein, we examined the protective effects of MSC transplantation on the development of PAH in this avian model.Methods: Mixed-sex broilers at 15 d of age were received 2× 106 MSCs or PBS intravenously. One day later, birds were exposed to cool temperature with excessive salt in their drinking water to induce PAH. Cumulative morbidity from PAH and right-to-left ventricle ratio were recorded. Lung histologic features were evaluated for the presence of endothelial damage, endothelial proliferation and plexiform lesions. Expression of proinflammatory mediators and angiogenic factors in the lung was detected. Matrigel tube formation assay was performed to determine the angiogenic potential of endogenous MSCs.Results: MSC administration reduced cumulative PAH morbidity and attenuated endothelial damage, plexiform lesions and production of inflammatory mediators in the lungs. No significant difference in the expression of paracrine angiogenic factors including VEGF-A and TGF-β was determined between groups, suggesting that they are not essential for the beneficial effect of MSC transplantation. Interestingly, the endogenous MSCs from birds receiving MSC transplantation demonstrated endothelial differentiatial capacity in vitro whereas those from the mock birds did not.Conclusion: Our results support the therapeutic use of MSC transplantation for PAH treatment and suggest that exogenous MSCs produce beneficial effects through modulating inflammation and endogenous MSC-mediated vascular repair.Graphical Abstract: Keywords: plexiform lesion, right ventricular hypertrophy, VEGF-A, TGF-β, angiogenesis, bone marrow